Valproate-induced thrombocytopenia - N. V. Izmozherova; A. A. Popov; I. P. Antropova; L. I. Kadnikov; D. A. Kruzhevnikova; O. A. Makarova (Лечащий Врач, 2024)
Background. Valproic acid is widely prescribed as an antiepileptic drug and mood stabilizer. Fatigue, tremor, sedation, hepatotoxicity, weight gain, hair loss and thrombocytopenia have been reported as side effects. Drug-induced thrombocytopenia occurs as the valproic acid dosage exceeds 1000 mg/day, or during concomitant antiplatelet agents administration, as well as in elderly patients. This side effect usually develops within 1-2 weeks after the drug initiation, but symptoms may also occur immediately after taking the drug. Patients present with petechiae, ecchymosis, and purpura, as well as epistaxis, hematuria, gingival bleeding, and hematochezia. Aim of the review. To analyze and systematize the literature data on the causes, mechanism and incidence of thrombocytopenia in response to valproic acid preparations.Materials and methods. An analysis of 42 domestic and foreign publications on the topic of thrombocytopenia due to valproic acid preparations was carried out.Results. The incidence of thrombocytopenia due to valproic acid drugs ranges from 5 to 31% in the general sample, up to 54% in elder people. Valproic acid has a direct toxic effect on the bone marrow, which reduces the production of neutrophil and erythroid lineages in the bone marrow through inhibition of erythrocyte differentiation and activation of the myelomonocytic pathway. In addition, valproic acid is incorporated into the platelet membrane due to its structural and chemical similarity to fatty acids in cell membranes. This promotes the production of autoantibodies directed against circulating platelets and leads to increased platelet destruction and thrombocytopenia.Conclusion. Thrombocytopenia is considered a common side effect of valproic acid drugs but has received less interest in clinical trials despite important therapeutic implications. Further research is needed to address this issue.